Green IT Engineering: Concepts, Models, Complex Systems Architectures - Kharchenko, Vyacheslav; Kondratenko, Yuriy; Kacprzyk, Janusz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume provides a comprehensive state of the art overview of a series of advanced trends and concepts that have recently been proposed in the area of green information technologies engineering as well as of design and development methodologies for models and complex systems architectures and their intelligent components. The contributions included in the volume have their roots in the authors' presentations, and vivid discussions that have followed the presentations, at a series of workshop and seminars held within the international TEMPUS-project GreenCo project in United Kingdom, Italy, Portugal, Sweden and the Ukraine, during 2013-2015 and at the 1st - 5th Workshops on Green and Safe Computing (GreenSCom) held in Russia, Slovakia and the Ukraine. The book presents a systematic exposition of research on principles, models, components and complex systems and a description of industry- and society-oriented aspects of the green IT engineering. A chapter-oriented structure has been adopted for this book following a "vertical view" of the green IT, from hardware (CPU and FPGA) and software components to complex industrial systems. The 15 chapters of the book are grouped into five sections: (1) Methodology and Principles of Green ITEngineering for Complex Systems, (2) Green Componentsand Programmable Systems, (3) Green Internet Computing,Cloud and Communication Systems, (4) Modeling and Assessment ofGreen Computer Systems and Infrastructures, and (5) Gree<n PLC-Based Systems for Industry Applications. The chapters provide an easy to follow, comprehensive introduction to the topicsthat are addressed, including the most relevant references, sothat anyone interested in them can start the study bybeing able to easily find an introduction to the topic through these references. At the same time, all of themcorrespond to different aspects of the work in progress being carried out by various research groups throughout the world and, therefore, provide information on the state of the art of some of these topics, challenges and perspectives. .
Part I: Methodology and Principles of Green IT Engineering for Complex Systems -- Part II: Green Components and Programmable Systems -- Part III: Green Internet Computing, Cloud and Communication Systems -- Part IV: Modeling and Assessment of Green Computer Systems and Infrastructures -- Part V: Green PLC-Based Systems for Industry Applications.
Keywords: Renewable energy sources; Microprocessors; Computer architecture; Computational intelligence; Software engineering; Renewable Energy; Processor Architectures; Computational Intelligence; Software Engineering